The Urgency of MUI Halal Fatwa about Food, Beverage, Medicine and Cosmetic Products for the Consumer Protection - Diky Faqih Maulana; Makhrus Makhrus; Hamidatul Hasanah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
This study examines how important it is to determine the halal fatwa of MUI for food, beverage, pharmaceutical and cosmetic products. Given that there are still many fraudulent practices committed by business actors or producers in the product manufacturing process, causing harm to consumers. While Law no. 8 of 1999 concerning Consumer Protection has guaranteed the safety of every citizen as a consumer. Then what is the form of legal protection by the state for consumers? And how important is the determination of the MUI's halal fatwa for consumer protection? This type of research is qualitative research with a normative juridical approach. Data collection techniques through exploration and documentation, namely collecting data regarding the establishment of halal fatwas, legal protection and Law no. 8 of 1999 concerning Consumer Protection. The results of this study indicate that the form of legal protection for consumers in Indonesia includes preventive, repressive and juridical legal protection as well as institutions whose role is to audit products such as LPPOM MUI, BPOM and other inspection agencies. The halal certification process can be carried out when a business actor applies for a halal certificate, then verification and validation, inspection by the LPPOM MUI halal auditor, the process of meeting the MUI fatwa commission, issuing a halal decree and issuing a halal certificate. Determination of MUI halal fatwa for each product is very important because it is ensured that it has passed the stages and procedures designed to provide protection to consumers. So that in the context of product transactions that occur in the field, no party benefits or is harmed and has applied the principle of balance and the principle of justice.